2010
DOI: 10.1002/adma.201001444
|View full text |Cite
|
Sign up to set email alerts
|

Spray‐Deposited Li‐Doped ZnO Transistors with Electron Mobility Exceeding 50 cm2/Vs

Abstract: The ever increasing demand for high performance electronic devices that can be fabricated onto large-area substrates employing low manufacturing cost techniques has given a boost to the development of alternative types of semiconductor materials, such as organics and metal oxides, with desirable physical characteristics that are absent in their traditional inorganic counterparts. Metal oxide semiconductors, in particular, are very attractive for implementation into thin-film transistors (TFTs) [1][2] mainly be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
88
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 108 publications
(91 citation statements)
references
References 30 publications
3
88
0
Order By: Relevance
“…An aqueous route allows for the preparation of IZO TFTs at a lower temperature compared with that used in the previously reported 2-methoxyethanol-based approach. [10][11][12] To investigate the uniformity of the devices, 36 TFTs with an IO active layer prepared via the aqueous route were fabricated at an The storage stability of a precursor solution is an important issue in sol-gel chemistry. The TFTs fabricated from pristine and 100-day-old aqueous solutions were compared with investigate the storage stability of the aqueous solution.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…An aqueous route allows for the preparation of IZO TFTs at a lower temperature compared with that used in the previously reported 2-methoxyethanol-based approach. [10][11][12] To investigate the uniformity of the devices, 36 TFTs with an IO active layer prepared via the aqueous route were fabricated at an The storage stability of a precursor solution is an important issue in sol-gel chemistry. The TFTs fabricated from pristine and 100-day-old aqueous solutions were compared with investigate the storage stability of the aqueous solution.…”
Section: Resultsmentioning
confidence: 99%
“…The high annealing temperature, which is usually 4400 1C, is not compatible with flexible plastic substrates, with conventional glass or with the stacked multi-layer structures because of the mismatch in the coefficient of thermal expansion between the layers during deposition. [10][11][12] A few studies on low-temperatureprocessable MOSs have been reported. [13][14][15][16] However, the authors of these studies used either complex and unstable precursors that required significant effort and multiple steps for synthesis or complicated chemical reactions that are not appropriate for the general fabrication technique.…”
Section: Introductionmentioning
confidence: 99%
“…Sol-gel techniques are used extensively for MO film growth, including films for high-performance TFTs (10)(11)(12)(13). However, the required sol-gel condensation, densification, and impurity removal steps typically require >400-500°C processing temperatures, which are incompatible with inexpensive glasses and typical flexible plastic substrates (14).…”
mentioning
confidence: 99%
“…Recently, metal oxide TFTs fabricated via solution-based processes have been considerably pursued for their potentials of offering simplicity, low cost, high throughput, and large area deposition. [9][10][11] Among various solution-based approaches, direct printing is a promising low-cost technique in fabricating TFTs. The printing technique offers several advantages in manufacturing electronics such as a direct writing of materials, reduction of chemical waste, and reproducibility with high-resolution scale, which are not affordable from other solution-based approaches.…”
mentioning
confidence: 99%